Implementasi pendidikan anti-bullying dalam menumbuhkan sikap toleransi siswa - Elvina Fitria Afifah; Deni Zein Tarsidi (Universitas Sebelas Maret, 2026)
Bullying remains a recurring issue in elementary school environments and has the potential to hinder students’ social development as well as disrupt the creation of a safe and inclusive learning atmosphere. One relevant effort to prevent bullying while simultaneously fostering positive social attitudes is the implementation of anti-bullying education integrated with character education. This study aims to describe the implementation of anti-bullying education in fostering students’ tolerance toward differences in character and background at SD Negeri Donoyudan. This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, teachers, students, and parents. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings reveal that anti-bullying education at SD Negeri Donoyudan is implemented in an integrated manner through school policies, the integration of character values into classroom instruction, teachers’ role modeling, and the habituation of positive behaviors in both academic and non-academic activities, including students’ play activities. The implementation contributes to the development of students’ tolerance, such as mutual respect, cooperation, and acceptance of differences in character and background among peers. The implications of this study indicate that anti-bullying education implemented consistently and integratively can serve as an effective strategy for strengthening character education and creating a safe, inclusive, and conducive elementary school environment that supports students’ social development.